2022
DOI: 10.1097/md.0000000000028973
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heavy metals in acute ischemic stroke patients

Abstract: Cerebrovascular disease is the second commonest cause of mortality globally and among the commonest causes of disability. However, research executed to probe the heavy metal exposure-stroke incidence relationship is scarce. Accordingly, we executed our study to probe the relationship of heavy metal concentrations (ie, concentrations of lead [Pb], mercury [Hg], cadmium [Cd], and arsenic) in the serum and urine of acute ischemic stroke (AIS) patients with several patient variables.For enrollment, we chose patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
4
0
1
Order By: Relevance
“…Exposure to several chemicals, such as lead (Pb), arsenic (As), mercury (Hg), cadmium (Cd), and CS2, is a potential risk factor for stroke. 69 However, only a few epidemiological studies have reported an association between occupational chemical exposure and cerebrovascular disease. 70 Chemical exposure is more common in developing countries.…”
Section: Chemical Exposuresmentioning
confidence: 99%
“…Exposure to several chemicals, such as lead (Pb), arsenic (As), mercury (Hg), cadmium (Cd), and CS2, is a potential risk factor for stroke. 69 However, only a few epidemiological studies have reported an association between occupational chemical exposure and cerebrovascular disease. 70 Chemical exposure is more common in developing countries.…”
Section: Chemical Exposuresmentioning
confidence: 99%
“…Arsenic (As) has been proven to induce various CVDs such as coronary heart disease, peripheral arterial disease, stroke, arrhythmia, and hypertension . Heavy metal As itself has cardiotoxicity, while fine particulate matter (PM 2.5 ) carrying heavy metal As (PM 2.5 -As) in nonferrous metal smelting areas has the characteristics of diverse species, high concentration, long transmission distance in the atmosphere and high absorption rate in organisms, which may cause greater cardiovascular damage. According to our previous study, approximately 25.0% of workers from smelting areas exhibited abnormal cardiopulmonary indexes, suggesting an increased risk of cardiovascular health issues among workers in these areas .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, according to the existing smelting technology and control measures, identifying the main exposure pathways of heavy metals associated with smelting sites and elucidating the ultimate health effects of heavy metal exposure are not only practical requirements for over 2 million employees and residents, but also hotspots and challenges for research in the fields of earth environmental science, epidemiology, and life sciences. Arsenic (As) has been proven to induce various CVDs such as coronary heart disease, 3 peripheral arterial disease, 4 stroke, 5 arrhythmia, 6 and hypertension. 7 Heavy metal As itself has cardiotoxicity, while fine particulate matter (PM 2.5 ) carrying heavy metal As (PM 2.5 -As) in nonferrous metal smelting areas has the characteristics of diverse species, high concentration, long transmission distance in the atmosphere and high absorption rate in organisms, which may cause greater cardiovascular damage.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Unbalanced levels of metals in the body have been shown to disrupt homeostasis and contribute to the progression of various diseases, including ischemic stroke [ 5 , 11 , 12 , 13 , 14 , 15 ]. However, the indication regarding the connection between exposure to heavy metals and stroke risk remains inconclusive.…”
Section: Introductionmentioning
confidence: 99%